Étude phytochimique et activité antioxydante de différents extraits de Zizyphus lotus L. - Bakhti, Hanene; Boucherba, Nadia (My University, 2020)
The present study was conducted on the shrub called Zizyphus lotus L. (Rhamnacea) which is known as Sedra in Algeria. This plant is very well-known in the traditional medicine to cure gastro-intestinal tract, liver and other different respiratory infections. It is also known for its anti-inflammatory, analgesic, anti-ulcer and anti-diabetic properties. In this study we tempted to evaluate in vitro the antioxidant activity of aqueous extract prepared from the leaves of the Z. lotus realized by two assays: the ferricreducing-antioxidant power assay (FRAP) and 2,2-diphenyl-1-picrylhydrazyl assay (DPPH).Qualitative analysis of these extracts by preliminary assays were revealed the presence of phenolic compounds and flavonoids; this result was confirmed by a quantitative analysis based on the colorimetric assays for phenolic and flavonoids compounds. The quantity of phenolic compounds for both aqueous extracts, decoction and infusion, is 158.16±5 and 100.02±4mg/g. the amount of flavonoids is 54.75±2.79 and 40.8±2mg/g for decoction and infusion extracts. Z. lotus leaves contain a significant amount of polyphenol and rich in flavonoids. The study of antioxidant activity by the method of ferricredu, cingantioxidant power (FRAP) and DPPH revealed high antioxidant activity. The FRAP results obtained show the presence of antioxidant power in the extracts studied with IC50 values of 11.798 ± 0.54 and 20.839 ± 0.08μg / mL for the decoction and the infusion, respectively and for the DPPH l ' higher antioxidant activity in the infusion with a value of 19.502 ± 0.71μg / mL compared to the decoction with a value of 12.12 ± 0.19μg / mL against ascorbic acid, catechin and trolox (0.45 ± 0.02 and 1.0493 ± 0.01 and 2.76 ± 0.04μg / mL, respectively). Therefore the leaves of Z.lotus are rich in polyphenols and especially in flavonoids. The latter are phenolic compounds known for their antioxidant and anti-free radical activities. This plant is also used in the modern pharmaceutical industry, to treat the digestive tract and the liver.
Keywords: Zizyphus lotus; antioxidant activity; Phenolic compound; flavonoids.